Intention to Exaggerate in Online Reviews Among Social Media Users in Indonesia - Nuraini Pasaribu; Istyakara Muslichah (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the influence of Dark Personality Traits on the intention to exaggerate online reviews among Indonesian social media users. The study focuses on narcissism, machiavellianism, psychopathy, and moral disengagement in the context of organic social media reviews. Data were collected through an online questionnaire, resulting in 244 valid responses, and analyzed using PLS-SEM with SmartPLS 4. The results show that machiavellianism positively influences exaggeration intention, whereas narcissism and psychopathy do not have significant direct effects. However, all three Dark Personality Traits positively influence moral disengagement, which significantly increases the intention to exaggerate online reviews. Moral disengagement emerged as the strongest predictor, highlighting its role in facilitating information distortion. This study contributes to the literature on consumer ethics, digital marketing, and the Dark Triad in a collectivist, non-Western context. The findings also provide practical implications for businesses and social media platforms in improving review monitoring systems, strengthening digital ethics awareness, and maintaining the credibility of online review ecosystems.